Comparative study of cross-country skiing on grip and skin skis - Korvas, P.; Goldschmidt, T.; Jaros, O.; Štastný, J. (Journal of Human Sport & Exercise, 2025)
The technology of cross-country skis for classic running is constantly evolving in the areas of ski construction or materials for ski construction. A study was focused to compare kinematic and kinetic parameters on grip and non-wax skis. Two groups of cross-country skiers participated in the with different skills quality. Kinematic and kinetic parameters of diagonal stride were observed: times of step cycle and phases, average and maximum pressure values of cycle phases. Pressure insole system was used for data collection. The Cohen size coefficient d was used. Differences between group of large effect size were found both on the flat and uphill for skiing on both types of skis (d = 0.82 - 17.26). Technically better skier showed minimal difference between skiing on both types of skis. For recreational skiers were found more differences on the uphill. Differences correspond to quality of movement patterns and ability of skiers to apply more efficiently technique on different types of skis on different type of terrain.